(untitled) (Innovaciones Educativas, 2020)
Due to the pandemic caused by the virus that causes the COVID-19 disease, Costa Rica’s education system must face challenges regarding education management, operations, and implementation at a national level. Higher Education is not an exception, so taking on the challenge to put forth strategies that allow the academic activities of a theoretical-practical nature to continue considering that what is fundamental is to safeguard the students’ lives as well as their health and well-being. The School of Educational Sciences of Universidad Estatal a Distancia is organized in different commissions to face such challenges. The commission made up of representatives of the Special Education, Preschool and Basic General undergraduate programs, laid on the line an approach endorsed by the University Council and welcomed by the other Faculties the proposal for the continuation of the Teaching and Professional Practices of this Faculty, to allow the continuation of the practical processes of the programs as mentioned above that include this process as a graduation option in their study program. The paper sets out the antecedents that support the creation of the academic proposal for the execution of the professional directed practices in the UNED, the main components of this, the methodology used for its design and the conclusions after this cooperative process between careers.